What Is Intertextuality Made Of?: A Response to Christine Hayes, ed., The Literature of the Sages: A Re-visioning - Amsler, Monika ca. 20./21. Jh. (NTT, 2024)
This review article predominantly focuses on the way intertextuality is addressed in The Literature of the Sages: A Re-visioning. A significant and informative portion of the work is dedicated to intertextuality, including a comprehensive history of the respective scholarship in the study of rabbinic texts. Indeed, rabbinic texts are full of intertextuality in terms of parallels, implicit or explicit referentiality, quotes, allusions, or simply shared vocabulary. The review will point out that although A Re-visioning does a fine job in summarizing and reviewing prior scholarship (esp. Hayes) and in gesturing at new directions (Gray), the contributions lack consideration of the physical aspects of texts, which enabled, shaped, and perhaps prevented intertextuality on an intellectual and a material-related level.